Legal framework governing the carriage of liquified natural gas (LNG) within coastal water - Asmawi Abdul Malik 1978- 452203; Mohd. Zamani Ahmad, supervisor 225362; Fakulti Kejuruteraan Mekanikal 8081 (2009)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2009